Зимові карнавальні традиції українців Сучавського повіту Румунії - Мойсей, А. (Народна творчість та етнологія, 2011)
In the present article interchange processes and reciprocal borrowings between Ukrainians and Romanians of Bukovina (first of all, in its southern part) are analyzed on the example of the winter carnival traditions (walking with Malanka, Herod, etc.) including caroling type walkings: caroling tradition, walking with the star, tradition of corn spilling, etc. Participants of the carnival customs are examined in particular, their functions and symbols, stages of performance, its separate elements. The article is based mostly on the materials of the field investigations performed by the author in 2006–2008 in 8 Ukrainian villages of Suchava district Romania.